Are there structural differences in the flight feathers among Procellariiformes related to the use of wings for underwater propulsion? - Moloto, Ditiro Judith (Department of Biological Sciences, 2020)
Wings of birds differ significantly in relation to their flight mode, life-history, and habitat. Most seabirds have high aspect ratio wings for efficient gliding, whereas those that dive tend to have shorter wings with lower aspect ratio. Some seabirds including petrels, auks and, to a lesser extent, gannets use their wings to ‘fly’ underwater as well as in the air. These different environments differ greatly in terms of density. The aim of this study is to investigate if there are differences in the flight feathers of seabirds that use their wings for both underwater and aerial propulsion and seabirds that only use their wings in air. The study was restricted to the order Procellariiformes because of the wide range of divers and non-divers. I sampled 33 species ranging from albatrosses to diving petrels, including species that can dive quite well and those that barely dive at all. Due to the 800-fold difference in density between water and air, I expected to find structural differences in the flight feathers of petrels that use their wings underwater and those that do not. The investigation was based on feather length, mass, micro-structure and stiffness relative to body mass. I expected the feathers of birds that dive well (those that attain depths more than 10 m deep) to be shorter (derived from their short wings), heavier, and stiffer compared to the feathers of birds that seldom dive. Further, I expected the differences to be more marked in the primaries compared to the secondaries, because primary feathers are subject to greater forces during flight. Allometric comparisons showed both expected and unexpected results. The primary feathers of diving birds were shorter relative to body mass while the secondaries showed no differences between the two groups. As a result, non-diving birds had heavier primaries compared to the diving birds while there was no difference in the secondaries. As expected, diving birds had heavier feathers relative to feather length. There were minimal to no differences in feather microstructure or stiffness between divers and nondivers. However, diving birds exhibited slightly less flexure relative to the length of their flight feathers than non-diving birds, suggesting that their feathers are slightly stiffer. Diving birds appear to have adapted to utilising the two contrasting media by evolving short, slightly heavy and stiff outer primaries, but these differences are not marked. The main adaptation to flight underwater probably is to partly close the wing, reducing its area and increasing the overlap between adjacent feathers.